Public management and governance in Malaysia : trends and transformations - Siddiquee, Noore Alam. (Milton Park, Abingdon, Oxon : Routledge, 2013)
'The past two and a half decades have seen major transformations in public sector management and governance across the globe. This book examines the ways public sector management and governance in Malaysia has changed and is changing under contemporary reform models. Chapters are written by well-established scholars and academics with intimate knowledge in their respective fields, and provide a thorough and insightful analysis of the reform trends and developments on a range of topics. These include performance management, compensation reforms, public budgeting, accounting and reporting, privatisation and public-private partnership, e-government, managing ethics and accountability, local government and inter-governmental relations. While the book surveys the topics that are central to public sector management and governance, it also focuses on the nature of reforms and changes that were introduced, as well as the forces that have shaped their design and implementation process, and the initial impacts and results'--
The public bureaucracy: an analytical overview -- Managing people: strategic human resource management initiatives in the public service -- Managing for excellence: performance management in the public service -- Pay for performance: compensation reforms -- Financial administration I: government budgeting -- Financial administration II: accounting and reporting -- Redefining relationships: privatisation and public-private partnerships -- Electronic government: developments and trends -- Managing ethics: drives for fighting corruption and enhancing integrity -- Local government and inter-governmental relations -- Development planning and policy: the new economic model in perspective -- Environment policy and governance.
Includes bibliographical references and index.
Keywords: Public administration -- Malaysia; Malaysia -- Politics and government